OP31 Dietary and Multi-Omic characterization of new onset treatment naive Crohn Disease identifies factors that may contribute to disease pathogenesis. (21st January 2022) - Haberman Ziv, Y; Braun, T; Amir, A; Levhar, N; Malik, A; Neuman, S; Picard, O; Yavzuri, M; Efroni, G; Hadar, R; Ben-Horin, S
Abstract: Background: Crohn Disease (CD) prevalence is rising worldwide. As altered genetics are improbable, this phenomenon likely relates to environmental-dietary changes linked with gut microbiome. We aimed to define host and microbial factors at CD diagnosis. Methods: Multiomics analyses of SOURCE cohort including clinical, biomarkers (CRP, fecal calprotectin), food frequency questionnaire (FFQ), serum metabolomics, mucosal terminal ileum (TI) transcriptomics, and fecal and mucosal biopsy samples for 16S microbial amplicon sequencing. Results: 25 newly-diagnosed CD and 33 controls (median age 28 years, 50% males). Gender, age, and BMI did not differ between groups, but CRP (p=0.001) and calprotectin (p=E-10) were significantly higher in CD. FFQ results showed that compared to controls, pre-diagnosis CD patients consumed significantly more added sugar (g/day), starch (g/day) nitrite (mg/day), and significantly less vitamin K, D, vegetables, and olive oil (Fig 1). Microbial analyses highlighted significant differences (FDR<0.1) in amplicon sequence variants (ASVs) abundance between stool and biopsies samples (73 ASVs) and between CD and Controls samples (82 ASVs). Biopsy vs. stool samples were enriched for Veillonella, Fusobacterium, Neisseria, and Ruminococcus gnavus. CD showed higher abundance of Enterobacteriaceae and Ruminococcus gnavus with reduction of several Ruminococcaceae and Lachnospiraceae taxa (Fig. 1). Ileal transcriptomics differential expression (FC>1.5, FDR<0.05) replicated previous results with significant induction in CD of DUOX2, CXCL9, and DEFB4A and pathways linked to innate and adaptive immunity, and to extracellular matrix. CD down regulated genes included GUCA2B, SLC10A2, and GSTA1, and pathways linked with epithelial transporters. Serum metabolomics highlighted significant variations (FDR<0.25) in Linoleic acid, aKG, Tryptophan, nicotinamide, Docosahexaenoic acid, oxalate, and GABA between CD and controls. We next tested for significant association (FDR<0.25) between diet and multi-OMICs (Fig. 2). Associations between gut microbiome and TI transcriptomics, and serum metabolomics showed that Erysipelotrichacea taxa positivity correlated with serum oxalate, and TI expression of CEACAM6 and DUOX2. Associations between diet and TI transcriptomics and serum metabolomics indicated that B12, tryptophan and riboflavin consumptions were negatively associated with the bile acid transporter SLC10A2 in the TI, and vegetables consumption was positively associated with oxalate degrading Oxalobacter. Conclusion: Conclusions: FFQ identifies difference in diet at the onset of CD that may contribute to pathogenesis. Integration between dietary and OMICs layers disclosed novel correlations warranting further exploration.